DIAGNOSIS AND TREATMENT OF BREAST CANCER IN SITU. RUSSIAN ASSOCIATION OF ONCOLOGICAL MAMMOLOGY CLINICAL GUIDELINES (PROJECT) - V. V. Semiglazov (Опухоли женской репродуктивной системы)
One of the first and foremost tasks of the Russian Association of Oncological Mammology (RAOM) is to develop clinical guidelines on diagnosis and treatment of breast cancer taking into account international experience. The guidelines must also be applicable in all regions of the Russian Federation allowing all Russian specialist to be informed about the latest strategies of diagnosis and treatment.These clinical guidelines are based on the following consensus documents:• St. Gallen Expert Panel (2011, 2013),• Expert Panel of the IX International Conference “White Nights – 2012”,• Expert Panel of the RAOM (2013),• International consensus on treatment of metastatic breast cancer ABC 1,• NCCN (2014)  and ESMO (2011) practical guidelines,as well as the results of large international randomized studies conducted in partnership with Russian oncological centers.The guidelines take into account the results of the analysis of a cumulative database on breast cancer treatment methods performed at• N.N. Petrov National Medical Research Oncology Center, Ministry of Health of Russia,• Saint  Petersburg City Clinical Oncological  Dispensary.Our guidelines are based on methods that are available everywhere in the Russian Federation, treatment schemes and drugs are presented in accordance with the marketing authorization of the Ministry of Health of Russia, drug therapy takes into account biological subtypes of breast cancer, different courses of the disease as well as nonuniform situation with drug availability in various regions of the Russian Federation.Obviously, such materials cannot serve as a direct guide for action (every patient’s disease is different), but they can lend a helping hand to a doctor striving to treat patients according to the latest achievements of modern oncology.All-Russian non-governmental organization Russian Association of Oncological Mammology. President of the RAOM, corresponding member of the RAS, Prof. V.F. Semiglazov; Vice-President of the RAOM, corresponding member of the RAS, Prof. G.M. Manikhas; Executive Director of the RAOM R.M. Paltuev, PhD.